Evaluation of the biodiesel fuel properties of fatty acid methyl esters from carica papaya L. - Charvet, Celina Therese S.P. (Animo Repository, 2011)
Fatty acid methyl esters (FAME) from Carica papaya L. (papaya) oil were investigated as a potential biodiesel fuel. Oil was extracted from papaya seeds by mechanical pressing, solvent extraction with hexane and solvent extraction with steam. The papaya seed oil contained 10.3% free fatty acid. Thus, a two-step conversion process of acid esterification followed by a conventional alkali-catalyzed transesterification was conducted. Upon testing, papaya FAME was found to have a density of 885 kg m -3 at around 15 °C, kinematic viscosity of 4.7 mm 1 s -1, an acid value of 0.26 mg KOH g -1, a cloud point of 20 °C, a flash point of 170 °C, a sulfur content of 0.029%, a sulfated ash content of 0.01%, a free glycerol content of 0.00%, a total glycerol content of 0.16% and a predicted iodine value of 76.0 g I 2 (100 g) -1. The FAME complied with three key biodiesel standards [Philippine National Standard (PNS 2020:2003), American Society for Testing and Materials (ASTM D6751-08) and European Standards (EN14214)], except for the kinematic viscosity, which exceeded the limit provided by PNS.